Liabilities of Business Failures as a Business Indicator - Simpson, Paul B.; Anderson, Paul S. (The Review of Economics and Statistics, 1957)
LIABILITIES of business failures move id in cycles which frequently lead general business, and for this reason have been designated as a leading series by the National Bureau of Economic Research.' The natural explanation of such lead lies in the profit experience of business concerns, particularly of submarginal concerns, since the lack of profits is undoubtedly the most important factor in causing business failures. The purpose of this paper is to examine this idea. The suggestion is made that profit margins per dollar of sales may lead business cycles, and since such margins are critical to the survival of submarginal firms, they are instrumental in causing liabilities of business failures to lead the cycle also.